The Influence Of Entrepreneurial Motivation, Entrepreneurial Commitment And Business Networks On The Success Of Msmes In Bengkulu City - Sari, Masita; Soleh , Ahmad; Made E G , Ida Ayu (Universitas Dehasen Bengkulu, 2025)
The purpose of this study is to determine the effect of entrepreneurial motivation, entrepreneurial commitment, and business networks on the success of MSMEs in Bengkulu City. This research employs a quantitative method, with data collected through questionnaires distributed to 87 culinary MSME actors in the Pantai Panjang area. The results of the analysis indicate that entrepreneurial motivation, entrepreneurial commitment, and business networks significantly affect the success of MSMEs in Bengkulu City. The multiple linear regression analysis produces the equation Y = -1.284 + 0.383X₁ + 0.293X₂ + 0.353X₃ + 1.738. The coefficient of determination (R²) from SPSS Version 25 is 0.843, which means that X₁, X₂, and X₃ collectively influence 84.3% of MSME success in Bengkulu City, while the remaining 15.7% is influenced by other variables. The t-test results at a 0.05 significance level show that partially, X₁, X₂, and X₃ significantly affect Y with significance values of 0.000 < 0.05, 0.002 < 0.05, and 0.001 < 0.05, respectively. The F-test results also indicate that X₁, X₂, and X₃ simultaneously have a significant effect on Y with a significance value of 0.000 < 0.05.